Recently Emerging Liquid Biopsy-based Non-invasive Methylation Biomarkers for Gastric Cancer Diagnosis, Prognosis and Therapy Response Prediction - Alom, Sarowar; Anal, B.S. Vaanrhaangh; Ghosh, Srimoyee (Current Cancer Therapy Reviews, 2025)
Cancer, a burden upon the global population, has consistently maintained its prevalence throughout history. Gastric cancer compounds this burden and ranks as the fifth leading cause of cancer-related deaths worldwide. The clinical significance of early cancer diagnosis cannot be overstated. DNA methylation biomarkers, a rapidly growing field of liquid biopsy-based diagnostics, provide a minimal to non-invasive way to detect cancer at an early stage. In addition to diagnosis and prognosis, liquid biopsy is important in longitudinal monitoring and therapeutic response prediction, where traditional biopsy faces setbacks. Despite many challenges, DNA methylation being a stable and detectable molecular change attracts the scientific community to develop novel biomarkers and analytical methods to incorporate them into clinical practice. In this review, we have discussed non-invasive, DNA methylation-based gastric cancer biomarkers that have emerged recently. We have also addressed the prognosis and therapeutic response prediction associated with these biomarkers.
Keywords: biomarker